Women and dictionary-making gender, genre, and english language lexicography - Russell, Lindsay Rose 1980- (Cambridge, United Kingdom Cambridge University Press, 2018)
"Dictionaries are a powerful genre, perceived as authoritative and objective records of the language, impervious to personal bias. But who makes dictionaries shapes both how they are constructed and how they are used. Tracing the craft of dictionary making from the fifteenth century to the present day, this book explores the vital but little-known significance of women and gender in the creation of English language".
1. Walking dictionary, sleeping dictionary: toward a gendered history of a rhetorical genre -- 2. Patronizing dictionaries: invocations of women at the invention of the genre -- 3. Compiling dictionaries: lexicography attributable to women and alternative generic traditions -- 4. Living with and working for dictionaries: women's contributions and critique as the genre expanded -- 5. Reinventing dictionaries: the generic interventions of feminist lexicography.
Includes bibliographical references (pages 217-245) and index.
Keywords: English language -- History. -- Dictionaries; Lexicographers -- Great Britain -- History; Women linguists -- Great Britain -- History